Analysis of miR-1183 Expression Level and Its role in Preeclampsia Pathogenesis via the Regulation of Its Target Gene CHURC1 - Didem Altındirek; Ece Gümüşoğlu-Acar; Ali Benian; Tuba Günel; Kılıç Aydınlı (Cerrahpaşa Medical Journal)
Objective: Preeclampsia (PE) is a multi-systemic disease in pregnancy and a leading cause of maternal and fetal mortality and morbidity worldwide. Elevated expression levels of certain circulating microRNAs (miRs) can be considered potential biomarkers, and have been reported in maternal plasma of pregnant women. We aimed to evaluate the expression profiles of circulating miR-1183 and its putative target mRNA in preeclampsia and their utility for prenatal diagnosis of preeclampsia.